Evaluating the Role of Viable Cells, Heat-Killed Cells or Cell-Free Supernatants in Bacterial Biocontrol of Fungi: A Comparison Between Lactic Acid Bacteria and Pseudomonas - Francesca Di Rico; Francesco Vuolo; Edoardo Puglisi (Microorganisms, 2025)
This study investigated whether viable cells, dead cells or cell-free supernatants (CFS) were responsible for the biocontrol effect of strains from two important bacterial genera, Pseudomonas and Lactobacillus, known for their antifungal properties against plant pathogens and food spoilage microorganisms. Specifically, the capability of these strains to produce extracellular hydrolytic enzymes on specified media was assessed, along with their effectiveness in inhibiting the mycelial growth of several phytopathogenic fungi (Fusarium oxysporum, Botrytis cinerea, Pythium ultimum and Rhizoctonia solani) using dual culture plate assays. Results from these inhibition assays revealed that P. fluorescens PF05 and L. plantarum LMG 23520 strains were the most effective in suppressing fungal growth, especially F. oxysporum. Therefore, further experiments were carried out to investigate the antifungal potential of the viable cells, heat-killed cells (HKC) and CFS from these strains against the germination of F. oxysporum spores. The viable cell trial proved successful, whereas HKC from the two bacterial isolates were ineffective against fungal spore germination. Conversely, the CFS of L. plantarum LMG 23520 was able to prevent fungal spore development for up to six days. The CFS of P. fluorescens PF05, instead, did not yield positive results. Additional studies are required to evaluate the potential inhibitory effects of the CFS from P. fluorescens PF05 and the HKC from both strains.